Inversion of mining-induced stress field based on focal mechanism solutions: a case study of the 63upper06 working face in Dongtan Coal Mine - Yan, Xianyang; Xu, Rui; Zhan, Kai; Wen, Xiaotao; Wang, Cong; Li, Zhenguo; Zhang, Quan (Frontiers in Earth Science, 2024)
Microseismic monitoring is pivotal for mine safety, offering early warnings for coal mining operations. By introducing the MTfit and MSATSI inversion methods to study the focal mechanisms of microseismic events and the stress field in coal mines, we applied these techniques for the first time to the 63upper06 working face in the Dongtan Coal Mine. We selected 107 high-quality microseismic events during the mining process and used MTfit to invert their focal mechanisms. Moreover, we used MSATSI to determine the direction of the maximum horizontal principal compressive stress in the region. This allowed us to establish a connection between mining activities, focal mechanisms, and rock strata fractures. Results show the predominance of normal and reverse faulting with significant CLVD components, underlining tensile and compressive failures as dominant in the mine’s seismicity. Further, the study subdivides the research area into three subregions for detailed stress analysis: Subregion 1 is located below the working face with a maximum principal stress of 20.3 MPa, oriented between N60°E and N75°E; Subregion 2 is above the working face and exhibits more complex stress conditions with a maximum principal stress of 30.1 MPa; and Subregion 3 is situated at the roof’s right side of the working face, with a maximum principal stress of 20.3 MPa, oriented at 30°northwest. It provides an important reference for seismic risk assessment and disaster prevention and control during mining.